Tools and methods for the management of healthcare real estate assets. The experience of the multidisciplinary laboratory of the Careggi University Hospital - Marzi, Luca (TECHNE - Journal of Technology for Architecture and Environment, 2014)
There is a number of different factors and data that require knowledge and responsibilities in the requalification and reorganization of a hospital building system. For the process to be successful and for its full implementation, there must be an inter-operation between this information and knowledge. This paper aims at contributing to this process by illustrating the experience of a multidisciplinary research laboratory consisting of architects belonging to the technological area, and computer/biomedical engineers, who defined and prepared a set of tools for an effective management of structural assets by using the “Policlinico di Careggi” hospital of Florence, that can be a reference for other similar contexts